Rancang Bangun Sistem Tanya-jawab Berbasis Aturan STMIK Muhammadiyah Paguyangan Brebes dengan Menggunakan Telegram Chatbot - Fauzan Ishlakhuddin; Azhar Basir; Nurlaela Nurlaela (Politeknik Harapan Bersama, 2020)
An educational institution should have an academic service system that is easy, accurate and fast in serving documents related to lecture information such as: Kartu Renrana Studi (KRS) and Kartu Hasil Studi (KHS) which will indirectly support the smooth teaching and learning activities. One of solution is to design an automated service system that can be accessed and served anytime, anywhere, and from anywhere, such as a chatbot. The method used in the design of this chatbot is to use a rule-based method to determine the answer (action) to be taken next. The main emphasis of this research only focuses on information services for the Biro Administrasi Akademik (BAAK). From the results of the adoption of this rule-based chatbot, a fairly high level of accuracy is obtained, which is up to 98.95% success rate (accuracy of answers) from 96 times of testing with different schemes.